Zoonoses: as doenças transmitidas por animais (Revista Brasileira Multidisciplinar, 2022)
Zoonoses are diseases or infections that are transmitted from animals to humans or vice versa, through different etiological agents. As a result of globalization and the evolution of mankind, humans started to have more contact with animals, due to feeding, domestication, work, and transportation, leading to the emergence of countless diseases that can be harmful to public health. Mankind coexists with both domestic and wild animals, and for this reason, some of these animals occupy urban centers and lodge near environments inhabited by humans, thus bringing different etiological agents, responsible for transmitting high-risk diseases such as rabies, leptospirosis, cryptococcosis, toxoplasmosis, hookworm disease, and yellow fever, including COVID-19, that is causing the current pandemic that worries the world population. The present work aims to alert the population and highlight the knowledge about zoonoses, discussing the relationship between them, highlighting those of greatest importance to Public Health, and listing aspects to prevent zoonoses in the world. This is a nonsystematic literature review of narrative type and qualitative nature. Scientific articles from the virtual databases Google Academic, Science Direct and SciELO, with a publication period of forty years, were consulted for the writing of the article. In conclusion, zoonoses present a high risk for Public Health, which requires control and prevention of these diseases.
Keywords: Zoonotic diseases. Infections. Domestic animals. COVID-19.